Determining influence of urban morphology on air temperature and heat index with hourly emphasis. (1st April 2023) - Kotharkar, Rajashree; Dongarsane, Parikshit; Keskar, Ravindra
Abstract: Assessing the impact of urban morphology on micrometeorological indicators has become of great significance due to rapid urbanization. Heat Index (HI) is one such indicator that determines the combined effect of air temperature (AT) and relative humidity (RH). The present study aims to evaluate the summer time impact of urban morphology on AT and HI with an hourly emphasis in Nagpur city. AT and HI were found symmetrically distributed only during nighttime, while RH and cooling rate (CR) data presented asymmetrical data distribution throughout 24hrs. A one-way ANOVA test was conducted to confirm their variations across areas for symmetrically distributed data. This test inferred that AT and HI are functions of LCZ. This data was then correlated with all morphological parameters. AT and HI showed a strong correlation (R 2 >0.7) during 23:00–06:00 h with building surface fraction, fabric density ratio, vegetation cover, albedo, sky view factor, and aspect ratio. During 23:00–06:00 h, every 10% increase in building surface fraction and albedo raises HI with 0.33 °C and 0.53 °C respectively, whereas a 10% increase in PSF and SVF reduces HI with 0.55 °C and 0.51 °C. This study concludes that nighttime AT and HI are significantly affected by urban morphology. However, daytime influence of these parameters and RH and CR throughout 24 h is inconclusive due to the asymmetrical data distribution of AT and HI. Modulation in development regulations by acknowledging the adverse effects of these morphological parameters is suggested for sustainable development. Highlights: This study confirms that air temperature (AT) & Heat Index (HI) are a function of LCZs. Asymmetrical distribution of micrometeorological data may influence assessing daytime morphological impact. Building footprint, fabric density, vegetation, aspect ratio, SVF, and albedo strongly influence AT & HI during 20:00–06:00 h. 10% increase in building footprint & albedo increases HI with 0.33 °C, 0.53 °C during 23:00–06:00. 10% increase in pervious surface & SVF, reduces HI with 0.55 °C, 0.51 °C during 23:00–06:00.